Effectiveness of Student Oriented Disaster Mitigation Learning Model on Students’ Disaster Awareness in Primary School - Syahrial Ayub; Kosim Kosim; I Wayan Gunada; Khaerus Syahidi (Universitas Hamzanwadi, 2022)
The increase in the incidence of disasters in recent years has given birth to many ideas in disaster mitigation efforts to save lives from the effects of disasters. The disaster mitigation system in Indonesia is still far from ideal. Mitigation technology is only limited to pre-disaster and early warning. There is no technology that facilitates knowledge and preparedness. Education and disaster mitigation procedures that must be imitated by the community are very necessary. The aim of the study was to determine the effectiveness of the disaster mitigation learning model on disaster awareness of students at SD N 6 Mataram. This study was limited to 25 fifth grade or high grade students at SD N 6 Mataram using a one group pretest-posttest design. Disaster mitigation awareness is measured using an objective test instrument with 25 items. Disaster mitigation awareness includes disaster knowledge (PK), disaster signs (TB), risk impact and efforts to reduce (DR), preparedness (KN), and procedures, first aid tools for victims (AP). The disaster mitigation awareness test instrument used has been tested for validity and reliability. The data obtained were statistically analyzed using SPSS 23.0 by performing normality test and paired t-test (paired t-test). The results showed that the student-oriented disaster mitigation learning model was effective in increasing the disaster awareness of students at SD N 6 Mataram.